Poder judiciário e competição política no Brasil: uma análise das decisões do TSE e do STF sobre as regras eleitorais - Ferraz Júnior, Vitor Emanuel Marchetti (2008)
Since 2002, the Supreme Electoral Tribunal (TSE) and the Federal Supreme Court (STF) have been making decisions on electoral rules by adopting a more aggressive stance. This study is based on the fact that the judicialization of elections is already an ongoing process. Due to this process, three matters are analyzed: 1) which institutional framework let the judicialization become a reality? 2) why the judicialization occurs? 3) what is its objective? Firstly, in order to answer these questions, the electoral model in Brazil has been defined. Afterwards, five expressive debate cases are investigated: the uniformity of party coalitions at state and federal levels, the number of city councilmen, thresholds for party representation, party funding and loyalty. In conclusion, it is proven that the judicialization took place as a result of the adopted electoral governance model. This process occurred rather because of judicial branch s attitude than because of eventual short comings of the legislative branch. And the whole judicialization was guided by mostly republican principles than by democratic ones